Drivers with Low Vision: Characteristics and Transportation Issues. (March 2018) - Crudden, Adele; Steverson, Anne C.; Cmar, Jennifer L.
Introduction: This study provides descriptive information about drivers with low vision and transportation issues, including their own self-imposed driving restrictions. Methods: An electronic survey administered online in late 2013 to early 2014 obtained data from 592 adults with visual impairments. Of those, 17 had a valid driver's license. These 17 provided information about their employment, activity limitations, public transportation use, services received, and transportation self-efficacy. Results: Approximately half of the low vision drivers were employed. Most had not received vocational rehabilitation or orientation and mobility (O&M) services. Most drivers limited their night driving and over 70% noted that transportation problems limited their participation in entertainment or leisure activities. Most drivers had access to public transportation, but did not frequently use it. Drivers were generally confident in their ability to perform transportation- related tasks, although overall, drivers using bioptic devices tended to be more confident. Drivers who did not use bioptic devices were least confident in arranging a fair price for daily transportation to work with a driver. Discussion: Drivers with low vision who limit their activities and employment due to transportation issues may not be receiving the vocational rehabilitation or O&M services that could help them compensate for these limitations. Further research examining the behaviors and service needs of low vision drivers is indicated, particularly for younger drivers. Study limitations include the small sample size, non-probability sampling method, and electronic data collection. Implications for practitioners: Low vision drivers may benefit from evaluation by O&M specialists and vocational rehabilitation providers to determine if additional services are needed. Persons with low vision should be informed about evaluation for bioptic devices, and vocational rehabilitation providers should network with bioptic providers and other professionals to obtain referrals of persons with low vision who are not yet vocational rehabilitation recipients.